Risk factors for recurrent otitis media with effusion - Baljošević Ivan; Čvorović Ljiljana; Stanković Katarina; Šubarević Vladan; Baljošević Zlata (Vojnosanitetski Pregled)
Background/Aim. Otitis media with effusion (OME) is a common disease among the children aged from 6 months to 4 years, but recurrences are common after the extraction of ventilation tubes. The aim of the study was to determine the risk factors for recurrent OME after extraction of ventilation tubes. Methods. The research was a prospective study with 305 children aged 0 to 10 years with OME. Forty three (14%) of them had recurrent OME. We analyzed the factors that could lead to the redevelopment of the disease after extrusion of the tubes. Results. It was found that the majority of children with recurrent disease was between the ages of 5 to 7 years (56%) and had allergy in significantly higher rate than children without recurrence. In most cases (37.7%), the retention time of ventilating tube was above 10 months and the recurrent disease was diagnosed in 46.5% cases within a period of 10 to 12 months after extrusion of tubes. Conclusion. Children with OME and after ventilation tube extrusion need to be followed up for 1 year after the removal of tubes. It is necessary to inform the parents that the disease can recur. Children in the kindergarten, in preschool age and with a respiratory allergy had higher possibility for recurrent OME.